2020
DOI: 10.3389/fphys.2020.594097
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Connexin 43 and Pannexin 1 During Acute Inflammation

Abstract: During acute inflammation, the recruitment of leukocytes from the blood stream into the inflamed tissue is a well-described mechanism encompassing the interaction of endothelial cells with leukocytes allowing leukocytes to reach the site of tissue injury or infection where they can fulfill their function such as phagocytosis. This process requires a fine-tuned regulation of a plethora of signaling cascades, which are still incompletely understood. Here, connexin 43 (Cx43) and pannexin 1 (Panx1) are known to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 80 publications
2
10
0
Order By: Relevance
“…Apart from purinergic receptors, several studies have highlighted elevated astrocytic CX43 in neurodegenerative diseases, leading to increased ATP release. Together with other nucleotide transporter such as pannexin-1, they could be targets of choice in order to decrease ATP release and aberrant purinergic signaling in neurodegeneration (203).…”
Section: Therapeutical Perspectivesmentioning
confidence: 99%
“…Apart from purinergic receptors, several studies have highlighted elevated astrocytic CX43 in neurodegenerative diseases, leading to increased ATP release. Together with other nucleotide transporter such as pannexin-1, they could be targets of choice in order to decrease ATP release and aberrant purinergic signaling in neurodegeneration (203).…”
Section: Therapeutical Perspectivesmentioning
confidence: 99%
“…Using an in vivo model for acute lung injury, namely lipopolysaccharide-instilled mice, it was shown that Cx43 hemichannels contribute to neutrophil transmigration towards the airspace [56]. Collectively, this could suggest a role for Cx43 hemichannels in neutrophil activation and transmigration in COVID-19 pathogenesis [3,7,21,22,57]. Furthermore, platelet aggregation and thrombosis, which occurs in the prothrombic phase and final phase of COVID-19, can develop towards multi-organ failure with death as outcome [12].…”
Section: Discussionmentioning
confidence: 99%
“…They seem to become preferentially activated by pathological stimuli, such as decreased extracellular calcium concentrations, mechanical stimulation, oxidative stress, ischemia/reperfusion injuries, and inflammatory conditions [3][4][5]. Among the messengers permeating connexin hemichannels, adenosine triphosphate (ATP) plays a key role in the induction and exacerbation of inflammation [6][7][8][9]. In this respect, inflammation is one of the hallmarks of the coronavirus disease 2019 .…”
Section: Introductionmentioning
confidence: 99%
“…Rosiglitazone also inhibited oxyhemoglobin-induced TLR4 activation and cytokine release in cultured vascular smooth muscle cells through the activation of PPAR-γ [ 42 ]. Moreover, pannexin-1 channels, a transmembrane protein of gap junction channels, regulate vessel function and permeability through releasing of signaling molecules, such as ATP, and contribute to both the innate and acquired immune systems via the modulation of cytokine values [ 240 , 241 ]. Pannexin-1 channels protein gene knockdown remarkably suppress the TLR2/4/NF-kB pathway and promoted cognitive functions in an experimental model of SAH [ 242 ].…”
Section: The Role Of Toll-like Receptors In Cvdsmentioning
confidence: 99%